Zdysocjowane odchylenie pionowe (dissociated vertical deviation – DVD) – przyczyny, objawy i leczenie - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The authors present etiology, diagnostic difficulties, clinical features and treatment of dissociated vertical deviation.